The cooperative learning approach to improve the english-speaking language skills in eight grade at educational unit Salcedo in the province of Cotopaxi - Doménica Anahí, Villacís Sandoval (2023)
Learning a second language is complex and requires a lot of dedication and effort to produce speech in L2 (English). Therefore, this study aims to identify the usefulness of Co-op-Co-op cooperative learning strategies in oral production in eighth grade students. The applied methodology was qualitative-descriptive. The participants were 14 eighth grade students from "Salcedo Educational Unit" at Cotopaxi Province, in the academic period September 2022 - June 2023. The techniques applied were a pretest and a posttest and the instrument was a rubric to evaluate the students. The results showed the Co-op Co-op strategy was useful to make students practice English language. The strategy helped students to be motivated to practice and feel more confident without fear of making mistakes. It also contributed to develop responsibility in their tasks. It was concluded that the Co-op Co-op strategy allowed students to be confident when using the language